Peran Promosi Kesehatan Dalam Pandemi COVID-19 - Musa ghufron (Universitas Muhammadiyah Surabaya, 2023)
A year after the COVID-19 pandemic entered Indonesia, the growth in the number of cases has still not been handled. The number of cases in Indonesia fluctuates along with the high and low mobility of community activities in Indonesia. Various efforts are needed to increase public knowledge and awareness of the dangers of COVID-19